Control of potato wart disease (Synchytrium endobioticum) by fungicide soil treatments - Çakir, E.; Demirci, F. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2024)
Synchytrium endobioticum is the causative agent of potato wart disease and can remain in the soil for several years via its sporangia. Effective protection against this disease includes quarantine and the use of disease-resistant potato varieties. However, so far it has not been eradicated. The aim of this study was to determine the effect of fungicides for soil treatment to protect against potato wart. Experiments were conducted with propamocarb hydrochloride 722 SC g/l, metalaxyl M + fludioxonil 10 + 25 g/l, gimexazole 360 g/l, tolklofos methyl + thiram 30 + 30%, dimethomorph + cuproxy chloride 6 + 40WP, famoxadone + cymoxanil 22.5 + 30%, Mandipropamide + Mancoceb 5 + 60%, Zoxamide + Mancoceb 8.3 + 66.7% in the growth chamber and field conditions — showed that Famoxadone + Cimoxanil 22.5 + 30% is able to protect against the disease by 100% in both experimental conditions.